Impact of blood pressure levels within first 24 hours after mechanical thrombectomy on clinical outcome in acute ischemic stroke patients. (6th February 2019) - Cernik, David; Sanak, Daniel; Divisova, Petra; Kocher, Martin; Cihlar, Filip; Zapletalova, Jana; Veverka, Tomas; Prcuchova, Andrea; Ospalik, Dusan; Cerna, Marie; Janousova, Petra; Kral, Michal; et al.
Abstract : Introduction: Despite early management and technical success of mechanical thrombectomy (MT) for acute ischemic stroke (AIS), not all patients reach a good clinical outcome. Different factors may have an impact and we aimed to evaluate blood pressure (BP) levels in the first 24 hours after MT. Methods: Consecutive AIS patients treated with MT were enrolled in the retrospective bi-center study. Neurological deficit was assessed with National Institutes of Health Stroke Scale (NIHSS) and functional outcome after 3 months with modified Rankin scale (mRS) with a score 0–2 for good outcome. The presence of symptomatic intracerebral hemorrhage (SICH) was assessed according to the SITS–MOST criteria. Results: Of 703 treated patients, completed BP levels were collected in 690 patients (350 males, mean age 71±13 years) with median of admission NIHSS 17 points. Patients with mRS 0–2 had a lower median of systolic BP (SBP) compared with those with poor outcome (131 vs 140 mm Hg, P<0.0001). The rate of SICH did not differ between the patients with a median of SBP <140 mm Hg and ≥140 mm Hg. (5.1% vs 5.1%, P=0.980). Multivariate regression analysis with adjustment for potential confounders showed a median of distolic BP (P=0.024, OR: 0.977, 95% CI: 0.957 to 0.997) as a predictor of good functional outcome after MT, and a median of maximal SBP (P=0.038; OR: 0.990, 95% CI: 0.981 to 0.999) in the patients with achieved recanalization. Conclusion: Lowering of BP within the first 24 hours after MT may have a positive impact on clinical outcome in treated patients.